2015
DOI: 10.1016/j.ccell.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Cooperativity Linked to Combinatorial Epigenetic Gain of Function in Acute Myeloid Leukemia

Abstract: Summary Specific combinations of Acute Myeloid Leukemia (AML) disease alleles, including FLT3 and TET2 mutations, confer distinct biologic features and adverse outcome. We generated mice with mutations in Tet2 and Flt3, which resulted in fully penetrant, lethal AML. Multipotent Tet2−/−;Flt3ITD progenitors (LSK CD48+CD150−) propagate disease in secondary recipients and were refractory to standard AML chemotherapy and FLT3-targeted therapy. Flt3ITD mutations and Tet2 loss cooperatively remodeled DNA methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
231
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(265 citation statements)
references
References 50 publications
32
231
1
1
Order By: Relevance
“…In fact, previous studies have uncovered co-occurrence of other disease alleles with TET2 mutations in myeloid malignancies [35,71,72], underscoring a critical role of convergent cooperative effects of these alleles. Recent study has demonstrated cooperative function of Tet2 loss and Flt3 ITD mutations in AML development in vivo through combinatorial epigenetic remodeling of specific genetic loci [73]. In agreement with co-occurrence of TET2 and EZH2 mutations in MDS and MDS/MPN patients, concurrent depletion of Tet2 and Ezh2 in mice developed MDS or MDS/MPN by derepression of oncogenic polycomb targets [74].…”
Section: Tet2mentioning
confidence: 74%
“…In fact, previous studies have uncovered co-occurrence of other disease alleles with TET2 mutations in myeloid malignancies [35,71,72], underscoring a critical role of convergent cooperative effects of these alleles. Recent study has demonstrated cooperative function of Tet2 loss and Flt3 ITD mutations in AML development in vivo through combinatorial epigenetic remodeling of specific genetic loci [73]. In agreement with co-occurrence of TET2 and EZH2 mutations in MDS and MDS/MPN patients, concurrent depletion of Tet2 and Ezh2 in mice developed MDS or MDS/MPN by derepression of oncogenic polycomb targets [74].…”
Section: Tet2mentioning
confidence: 74%
“…Similarly, in murine hematopoietic stem cells (HSCs) and progenitors, TET2 deficiency leads to impaired differentiation and increased self-renewal potential that drives a disease mimicking human CMML [14,15]. However, as is true in humans, the development of AML in TET2-deficient mice requires additional alterations, such as a gain-of-function mutation of FLT3 [16]. Whether TET1/3 can compensate for loss of TET2 has yet to be addressed, but no increase in TET1/3 expression has been detected in TET2-deficient mice [14].…”
Section: Introductionmentioning
confidence: 99%
“…Knock-in mouse models have been instrumental in deciphering the hematopoietic and leukemogenic effects of FLT3-ITD alone [4][5][6] and in combination with mutations co-occurring with FLT3-ITD in human AML [7][8][9][10][11][12] ; as well as in studying the effectiveness of different therapeutic approaches in FLT3-ITD-positive leukemias. F692L), was present at allele frequencies of 0.55-0.94.…”
mentioning
confidence: 99%